2011
DOI: 10.1162/neco_a_00103
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Reinforcement Learning and Optimal Decision-Making Theories of the Basal Ganglia

Abstract: This article seeks to integrate two sets of theories describing action selection in the basal ganglia: reinforcement learning theories describing learning which actions to select to maximize reward and decision-making theories proposing that the basal ganglia selects actions on the basis of sensory evidence accumulated in the cortex. In particular, we present a model that integrates the actor-critic model of reinforcement learning and a model assuming that the cortico-basal-ganglia circuit implements a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 74 publications
4
84
0
Order By: Relevance
“…It has been suggested that when the brain does not have full access to the correct value of the physical attributes of the stimuli, the cerebral cortex uses noisy observations to infer them (39,40) and that the midbrain DA neurons and striatal neuronal circuits evaluate the state of the environment to select the appropriate actions based on the results of that inference (35)(36)(37). In this scheme, the outcome of the inference process is a posterior probability about the state of the environment, which is interpreted as a measure of the belief about that state (41).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that when the brain does not have full access to the correct value of the physical attributes of the stimuli, the cerebral cortex uses noisy observations to infer them (39,40) and that the midbrain DA neurons and striatal neuronal circuits evaluate the state of the environment to select the appropriate actions based on the results of that inference (35)(36)(37). In this scheme, the outcome of the inference process is a posterior probability about the state of the environment, which is interpreted as a measure of the belief about that state (41).…”
Section: Resultsmentioning
confidence: 99%
“…This is the basic scheme followed in early proposals about how to extend the RL framework to model the DA activity in decision-making tasks (35)(36)(37). In this approach, the belief state is used to predict rewards, to compute the error in the prediction, and to select the action that indicates the final choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the underlying intuition that intelligent behavior requires both the ability to control actions as well as to learn from consequent feedback, it is not well understood how these learning and control systems interact. One reason for this is that computational models of learning [1,2] and control [3][4][5] have historically emerged from disparate lines of empirical research (see [6,7] for exceptions), adding difficulty to the already challenging task of inferring cognitive phenomena from gross behavioral measures. Recently, however, insights from cognitive and computational neuroscience have begun to shed light on the interaction of cognitive processes in neural circuits, providing additional empirical anchors for grounding theoretical assumptions [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The basal ganglia (BG), a subcortical network that shares dense, reciprocal connections with much of cortex, as well as many subcortical neuromodulators, is known to play a critical role in both learning and control processes -acting as a central integration hub where cortically-distributed control commands [12][13][14] , sensory evidence [15,16] , and decision variables [17][18][19] can be weighed and synthesized with feedback-dependent learning signals to facilitate goal-directed behavior [7,20,21] . Cortical information enters the BG through three primary pathways: the first two of these pathways, entering via the striatum, are the direct (i.e., facilitating; Fig 1A, green) and indirect pathways (i.e., suppressing; Fig 1A, blue).…”
Section: Introductionmentioning
confidence: 99%